Principles of environmental science : - Cunningham, William P. (McGraw-Hill, 2006)
Rather than the 25 to 30 chapters found in most environmental science textbooks, the authors have limited "Principles of Environmental Science: Inquiry and Applications" to 15 chapters - perfect for the one-semester, non-majors environmental science course. True to its title, the goal of this concise text is to provide an up-to-date, introductory view of essential themes in environmental science along with offering students numerous opportunities to practice scientific thinking and active learning.